A Novel Synthetic Route to Carbon Nanotubes Supported ZrO2/TiO2 Nanoparticles - yan Xu, Hai; Liu, Changling; Li, Yan; Xu, Ling; Wang, Xudong; Liu, Chenshu (Asian Journal of Chemistry, 2013)
In this study, ZrO2/TiO2 nanoparticles were synthesized and loaded upon carbon nanotubes with TiCl4, ZrOCl2 and HNO3, using hydrothermal synthetic method. Prepared particles were then subjected to structural characterization with XRD and TEM. Our XRD results suggest that, in the ZrO2/TiO2-carbon nanotubes complexes, phase transition of TiO2 crystallites occurs from rutile tinania to anatas as the doped ZrO2 content increases. TEM results indicate that, ZrO2/TiO2 particles can be supported homogeneously on the surface of carbon nanotubes only when the complex has 10 % ZrO2, under our experimental conditions.